Research on preparing inservice teachers to work effectively with emergent bilinguals - Freeman, Yvonne S.; Freeman, David E. (Bingley, U.K. : Emerald, 2015)
Between 1990 and 2010, the English language learner (ELL) population in U.S. schools grew by 80 percent. While the highest concentration of English language learners, now more commonly referred to as emergent bilinguals (EBLs) remains in the traditional immigrant destination states of California, Texas, New York, Florida, Illinois, and New Jersey, in all 50 states there are growing numbers of emergent bilinguals. Interest in these learners has encouraged research and publications, but most of this research has centered on the students themselves and the politics surrounding their education. Publications featuring the research of teacher educators preparing teachers to work with EBLs in schools are much needed. Teacher educators must know how to help inservice teachers provide effective instruction to the increasing number of linguistically diverse students in the schools.
Joining the team : a study of unintentional professional development / Cecilia Silva, Molly Weinburgh, Kathy Horak Smith -- The power of culturally relevant texts : what teachers learn about their emergent bilingual students / Ann E. Ebe -- Promoting exploratory talk with emergent bilinguals / Yvonne S. Freeman, Alma D. Rodríguez -- Teachers' understanding of practice : planning and implementing preview/view/review in the dual language classroom / Sandra Mercuri -- Mainstream teachers in two-way immersion programs : becoming content and language teachers / Ester de Jong, Katherine Barko-Alva -- Freedom within structure : practices for teacher sustainability, efficacy, and emergent bilingual student success / Dawn Wink -- An art of being in between : the promise of hybrid language practices / Brendan H. O'Connor, Layne J. Crawford -- Reshaping the mainstream education climate through bilingual-bicultural education / Jason Goulah, Sonia W. Soltero -- Why didn't anyone tell me this before? / Susan Spezzini, Julia S. Austin, Josephine Prado -- Empowering language and learning with Muslim immigrant youth / Heather Homonoff Woodley -- "We only teach in English" : an examination of bilingual-in-name-only classrooms / Kip Austin Hinton.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Teaching skills & techniques; Teachers -- Training of -- United States; Education, Bilingual -- Research -- United States; Multicultural education -- Research -- United States; Education, Bilingual -- Research